Education in Tourism Industry: Challenges and Opportunities - U. Yu. Abduvakhabova (Universitas Muhammadiyah Sidoarjo, 2020)
The aim of the article is to define, analyze and suggest ways of solution of the influence of learning foreign languages problems to develop international tourism in Uzbekistan. It is emphasized that the knowledge of foreign languages is important for the further development of international tourism, because the tourism industry is closely connected with foreign languages. Comparative analyses of different methodologists and scientists’ points of views was carried out in literature review to match different approaches of most effective way in teaching foreign language for specialist in tourism industry. For the analysis, pedagogical technologies that are often used in the teaching process and technologies that are little known in pedagogical work, which could be very effective, were selected. The selection was carried out through analysis of literature in the field of pedagogy: studying the experience of innovators (Shchukin A.,Sparks R.L., Ganschow L. and others), as well as the experience of teachers of modern school. It is concluded that international tourism can contribute to increasing the motivation and efficiency of learning a foreign language.